Perceptions regarding academic social networks for scholarly communications. Issue 8 (1st July 2020) - Al-Muomen, Nujoud; Chaudhry, Abdus Sattar; Al-Othinah, Oroba
Abstract : Purpose: This study aims to investigate the perceptions of academics regarding the use and usefulness of academic social networks (ASNs) in the scholarly communication practices of faculty members in Kuwaiti Universities. Design/methodology/approach: The study was conducted through a survey. In total, 100 faculty members from the disciplines of business administration, humanities and social sciences from three universities in Kuwait filled in an online questionnaire. The statistical feature of the Web-based tool was used for data analysis. Findings: The results show that most faculty members are aware of the importance of ASNs. They perceive that these networks are useful, as more publications have become available, it has become easier for scholars to connect with colleagues who share similar research interests. Research limitations/implications: The study is descriptive and restricted to a specific country (Kuwait). It also only covered faculty members from three academic disciplines. Furthermore, the use of a questionnaire, while appropriate for descriptive research, restricted us from conducting probing designed to gain deeper insights regarding participants' motivations and explanations for not realizing the potential of these networks. Practical implications: Future research should expand the scope of this study to cover faculty members from other disciplines (e.g. science, engineering and medicine), while also including more universities from other countries in the Arabian Gulf region. Future research should also examine how academics' information-finding practices are changing as a result of the availability of information sources through ASNs. Originality/value: No similar study has been conducted previously in Kuwait. This study provided useful information regarding the use and perceptions of ASNs in the context of faculty members of Kuwaiti universities. This information is of interest to scholars, information providers and those who design such networks.